2014
DOI: 10.4103/0976-9668.136189
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cervical biometry using transvaginal ultrasonography in predicting preterm labor

Abstract: Context:Preterm delivery is associated with high perinatal mortality and morbidity. Although detection of fetal fibronectin in cervical can predict preterm labor, but it is not available in lower source setting area. So, cervical length measurement by ultrasound can be used as an alternative to fetal fibronectin for predicting preterm labor.Aims:To find out the effectiveness of assessment of cervical length by endovaginal ultrasonography in predicting preterm delivery.Settings and Design:The study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This is statistically significant and suggest that shorter the cervical length more is the risk of preterm delivery. This is consistent with the result of study by Mathur S et al 6 and Tanvir et al 7 which also shows positive correlation. Hence, it can be concluded that nearly 1/2 to 2/3 of women with short cervical length <25mm deliver preterm unless certain precautions are taken.…”
Section: Discussionsupporting
confidence: 93%
“…This is statistically significant and suggest that shorter the cervical length more is the risk of preterm delivery. This is consistent with the result of study by Mathur S et al 6 and Tanvir et al 7 which also shows positive correlation. Hence, it can be concluded that nearly 1/2 to 2/3 of women with short cervical length <25mm deliver preterm unless certain precautions are taken.…”
Section: Discussionsupporting
confidence: 93%
“…It needs to be considered that in this study we excluded primipara women which were included in other studies. (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Research in useful prediction models may reduce health care costs and perinatal complications. Cervical length is a sensitive and simple method to predict the risk for PD (19) . While a short CL is for predicTinG imminenT preTerm delivery (X aXis: "1specifici-Ty"; y aXis: sensiTiviTy).…”
Section: Discussionmentioning
confidence: 99%